Scalable Tool for Holding and Placement of Orthodontic Brackets - Ibrahim Alshahrani; Ali Alhaizaey (KARACHI MEDICAL AND DENTAL COLLEGE, 2023)
An essential component of orthodontic therapy that affects the effectiveness of care and patient results is the positioning of orthodontic brackets precisely. This abstract introduces the idea of a "Scalable Tool for Holding and Placement of Orthodontic Brackets," which is intended to overcome the difficulties of manually placing orthodontic brackets. This ground-breaking device combines bracket holding, positioning aids, pressure control, and measuring features, making it flexible for use with different bracket types and tooth kinds. It attempts to increase bracket placement accuracy, efficiency, and consistency while decreasing bond failures and treatment adjustments. The tool's user-friendliness and hygienic standards are enhanced by its ergonomic design and sterilizable components. This tool has the potential to streamline orthodontic treatments, reduce patient chair time, and enhance overall treatment by expediting the bracket insertion procedure. To enable successful integration into orthodontic practice, future research and development will concentrate on safety, legal compliance, and ethical factors.